Interaction Techniques for Remote Maintenance in an AR Shared Environment - Krings, Sarah, Claudia; Biermeier, Kai; Yigitbas, Enes (CCSD, 2024)
Part 2: Late-Breaking Results International audience In today’s world, the importance of remote collaboration for maintenance scenarios is strongly increasing. Especially in the industrial context where machinery and other objects have to be maintained, traditional collaboration tools such as video conferencing systems are not helpful enough to communicate and interact about situation-specific spatial information. In this work, we identify and discuss current challenges in enhancing communication and interaction for mobile augmented reality (AR) based collaboration approaches. To address the identified challenges we introduce a mobile AR solution that integrates various features like voice communication, text chat, screen share, AR annotations, and AR animations to enhance the task of remote collaboration between an on-site technician and a remote expert. Based on a coffee machine maintenance example scenario we have conducted a user study and compared the benefits and drawbacks of different interaction techniques in our mobile AR collaboration solution.